PENGARUH MOTIVASI EKONOMI, MOTIVASI GELAR DAN ORIENTASI KARIR TERHADAP MINAT MAHASISWA DALAM MENGIKUTI UJIAN CERTIFIED PUBLIC ACOUNTANT (CPA) INDONESIA (Studi Empiris pada Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Negeri Malang) - Nailiatul Virohiyyatun Ni’mah; Nur Diana; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aimed to determine the effect of economic motivation, degree motivation, and career orientation on the interest of accounting students in taking the Indonesian Certified Public Accountant (CPA) Exam. This study's sources are secondary data and primary data taken from filling out questionnaires given by researchers to the Accounting Students Class of 2018 at the Islamic University of Malang and State University of Malang. The independent variables are Economic Motivation, Degree Motivation, and Career Orientation. This type of research includes quantitative research with correlational research characteristics. Sampling from the population used the purposive sampling method, namely the sampling technique using specific criteria. The total population is 603 respondents, while the sample obtained based on calculations from the Slovin formula is 85 respondents. The analytical method used is Multiple Linear Regression Analysis. This study indicates that Economic Motivation and Career Orientation have a significant effect on student interest in taking the Indonesian Certified Public Accountant (CPA) Exam. Meanwhile, Degree Motivation does not significantly affect student interest in taking the Indonesian Certified Public Accountant (CPA) Exam.Keywords: Economic Motivation, Degree Motivation, Career Orientation, and Certified Public Accountant (CPA) Indonesia.